Kitkatla Panorama - A. de Menil (1968)
Four-part Panorama of Kitkatla, British Columbia. The village is home to the Gitxaala Nation. It is one of the longest continually inhabited communities in all of North America. The ancestry of the people living here dates back 10,000 years.